Inovasi Daur Ulang Lilin Batik Untuk Efisiensi Biaya Dan Peningkatan Kualitas Produk Ramah Lingkungan Pada UKM Batik Manggur Probolinggo - Widayanto, Mutinda Teguh; Abdillah, Hartawan; Baihaqi, Mas Ahmad; Hidayat, Ibnu; Trifanto, Angel Agus (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
The development of SMEs as a support for the national economy must continue to be supported. In producing Batik, it cannot be avoided that there is waste in the form of wax from used batik which can pollute the environment. UKM Batik Manggur is one of the UKM in Probolinggo, East Java Provinci, which has several problems in developing its business, including processing batik wax waste. This community service activity provides a solution by recycling batik wax waste so that it does not pollute the environment and can be reused for the batik process. The service activities carried out include training in batik wax processing and outreach to batik makers in the Probolinggo City area. Recycled Wax has good quality so it can be reused for the batik process. Using recycled wax has several benefits, including improving batik quality and reducing production costs. With this community service activity, it is hoped that Mitra can develop his business with higher quality and environmental friendly products and reduce production costs.